2002
DOI: 10.1063/1.1514584
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of CO elimination from reactions of yttrium atoms with formaldehyde, acetaldehyde, and acetone

Abstract: Reactions of neutral, ground-state yttrium atoms with formaldehyde, acetaldehyde, and acetone (YϩRRЈCO, where R,RЈϭH,CH 3) were studied in crossed molecular beams. At collision energies greater than 24 kcal/mol, four product channels were observed corresponding to elimination of CO, H 2 , H, and nonreactive scattering. For the dominant CO elimination channel, a large fraction ͑34%-41%͒ of the available energy appeared as kinetic energy of the products. RRKM modeling indicated this was a result of two factors: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 34 publications
6
28
0
Order By: Relevance
“…The hydride-containing compound is calculated to be 3. for aC1FeC2, aC2FeH1, and aH1FeC1, respectively), which is strictly analogous to that of the precursor of the reaction Y + CH 3 CHO!CH 3 YH + CO, studied in crossed molecular beam experiments by Schroden et al [40] This structural feature can be understood by the results of NBO analysis. On the basis of our calculations, in 6 3b' 4s Fe þ and 1s H1 orbitals form a s FeH aorbital, while the linkage of the other two groups (CO and CH 3 ) with Fe + is strengthened by the strong a-electron donations from the 2s2p z hybridized orbital of C1 and 2p x 2p z hybridized orbital of C2 to s* FeH (DE: 17.9 and 30.5 kcal mol À1 ), respectively (where the C s symmetry plane is defined by the xz coordinates with the z axis polarized along the CO).…”
Section: Hydride-containing Species (Ch 3 )M + H(co)mentioning
confidence: 65%
“…The hydride-containing compound is calculated to be 3. for aC1FeC2, aC2FeH1, and aH1FeC1, respectively), which is strictly analogous to that of the precursor of the reaction Y + CH 3 CHO!CH 3 YH + CO, studied in crossed molecular beam experiments by Schroden et al [40] This structural feature can be understood by the results of NBO analysis. On the basis of our calculations, in 6 3b' 4s Fe þ and 1s H1 orbitals form a s FeH aorbital, while the linkage of the other two groups (CO and CH 3 ) with Fe + is strengthened by the strong a-electron donations from the 2s2p z hybridized orbital of C1 and 2p x 2p z hybridized orbital of C2 to s* FeH (DE: 17.9 and 30.5 kcal mol À1 ), respectively (where the C s symmetry plane is defined by the xz coordinates with the z axis polarized along the CO).…”
Section: Hydride-containing Species (Ch 3 )M + H(co)mentioning
confidence: 65%
“…30 Second, the proton as a single ion-projectile is favored because of its missing electronic structure and capability of capturing electrons as well as its abundance in the solar wind and in the ISM. Third, so far, a great deal of work about formaldehyde has concentrated on unimolecular photodissociation, [31][32][33][34][35][36][37][38] collision-induced ionization and dissociation by electrons, 28, 39-43 atoms, [44][45][46][47][48][49][50] and ions. [51][52][53] Unfortunately, little is known about the physical process of proton impact on formaldehyde, although Jalbout 30 advanced the study of a single formaldehyde reacting with a single proton source (H + 3 , H 3 O + ).…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the fundamental aspects of this reaction, several studies have been reported on the investigation of the relevant mechanism [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. As one of the sim ple carbonyl containing organic molecules, acetalde hyde is used in many practical application fields such as organic synthesis, catalysis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Their results show that for Co + , Fe + , and Cr + , decarbonylation proceeds through C-C activation rather than aldehyde C-H activation, whereas both C-C and aldehyde C-H activation may result in the decarbonylation of CH 3 CHO by Ni + cation. Compared with the first row cation, heavier metal atoms and cations have received less attention, and only a few theoretical and experi mental studies have been reported [12][13][14]. Bayse et al [14] have investigated the reaction between yttrium atom and acetaldehyde in detail.…”
Section: Introductionmentioning
confidence: 99%